Utilization of Toddlers by Their Families in the Activities of Beggers in Padang City - Syahrepah, Syahrepah; Putri, Adella Suryani; Fitriani, Wahidah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Children are a trust from Allah SWT who must always be guarded, cared for, guided, and protected. Children are the responsibility of their parents, starting from fulfilling their physical and psychological needs, economic needs, education, environment, and behavior of a child. In reality, there are still many parents who have not fully fulfilled their responsibilities and on the contrary, there are some parents who exploit their children to be able to support their families. In fact, many parents use their children as a means to beg for the reason of meeting their family's living needs. This is done by carrying their children in their arms at crossroads, placing them on shop verandas while begging in crowded places in Padang City. Based on the above phenomenon, the author wants to examine further the use of toddlers by their families in begging activities in Padang City, which the author has written in a scientific paper. This study aims to determine the forms, causal factors, and impacts of the use of toddlers, as well as the responses and handling patterns of the Padang City Social and Manpower Office regarding the problem of the use of toddlers by their families in begging activities in Padang City. This study is a field research using qualitative methods in descriptive form. While the data collection technique through observation and interviews. The informants in this study were beggars who use toddlers using quato sampling techniques. Based on the results of the study obtained; first, the forms of exploitation of toddlers by their families in begging activities in Padang City, physically, namely creating a sense of pity from others carried out by their parents by pinching and shouting at their children, while psychologically, namely taking advantage of the child's condition that looks gloomy and pitiful to support the creation of the pity atmosphere. Second, regarding the factors causing the exploitation of toddlers by their families in begging activities in Padang City, namely economically, influenced by the environment, parents' wrong perceptions about the meaning of children, low parental education and parents do not know and understand about child exploitation. Third, the impact of the exploitation of toddlers by their families in begging activities in Padang City, physically, namely the child's health is disturbed, psychologically, namely becoming quiet, apathetic, emotional, pitiful and gloomy views. The fourth finding in this study concerns the response and handling patterns of the Padang City Social and Manpower Office regarding the problem of the use of toddlers by families in begging activities in Padang City. The Padang City Social and Manpower Office's response was a low self-esteem, a lack of shame in begging, and the belief that begging does not actually exist if the husband is responsible for the child and family. The handling patterns include implementing preventative, repressive, and rehabilitation efforts.